Association Between Body Self-Perception and the Incidence of Hypertension: The SUN “Seguimiento Universidad de Navarra” Cohort 1999–2022 - Patricia Caro; Carmen De La Fuente-Arrillaga; Vanessa Bullón-Vela; Rafael Pérez-Araluce; Miguel Ángel Martínez-González; Maira Bes-Rastrollo (Biomedicines)
Objective: This study aims to analyze the association between self-perceived body image and the incidence of hypertension. Methods: A prospective cohort study was conducted, classifying body image perception into three categories: adequate, underestimation, and overestimation, based on Stunkard’s Figure Rating Scale and self-reported nutritional status. Cox proportional hazards models were used to determine the association between body image perception and the risk of developing hypertension, adjusting for potential confounders. Results: During a mean follow-up period of 12.7 years, 2359 incident cases of hypertension were identified. In the main adjusted model, body image underestimation was significantly associated with an increased risk of hypertension among women (HR 1.25; 95% CI 1.01–1.55). This association lost statistical significance when adjusting for baseline BMI in the sensitivity analysis. Conclusions: Self-perception of body image may influence health behaviors that impact weight control, potentially leading to higher BMI and, consequently, greater cardiometabolic risk. Although further research is needed to clarify its role, body image perception should begin to be considered in clinical practice as a relevant factor in chronic disease prevention.